Adverse events and near miss reporting in the NHS. Issue 4 (1st August 2005) - Shaw, R; Drever, F; Hughes, H; Osborn, S; Williams, S
Abstract : Objectives: To conduct a multicentre study on adverse event and near miss reporting in the NHS and to explore the feasibility of creating a national system for collecting these data. Design: Prospective voluntary reporting by staff with anonymised transfer of data was used by a national system to collect data from 18 NHS trusts. Participants: Staff from 12 acute trusts, three mental health trusts, two ambulance trusts, and one primary care trust. Main outcomes measured: Number of incidents, date and time of incident, patient age and sex, clinical speciality, location, outcome, risk rating, type and description of incident. Results: A total of 28 998 incidents were reported including 11 766 (41%) slips, trips and falls, 2514 (9%) medication management incidents, 2429 (8%) resource issues, and 2164 (7%) treatment issues. 138 catastrophic and 260 major adverse outcomes were reported. Slips, trips and falls (n = 11 766) were the most common type of incident. Conclusions: Voluntary reporting by staff when linked to a multicentre data collecting system can yield information on a large number of incidents. This provides support for the principle of creating a national IT system to collect and analyse incident data.